Situated Learning in Virtual Worlds: The Learning Ecology of Second Life - Elisabeth R. Hayes (Adult Education Research Conference, 2006)
This research investigated the “learning ecology” of the virtual world, Second Life. Study goals were to: (a) determine how the design and social dynamics of one virtual world support as well as constrain various types of learning, and (b) suggest implications for the use of virtual worlds in adult education.
Keywords: virtual worlds; situated learning; technology; community